2011
DOI: 10.1159/000320842
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Forced Coughing versus Local Anesthesia during Cervical Punch Biopsy

Abstract: Background/Aims: To compare local anesthesia and forced coughing in terms of subjective pain perception during cervical punch biopsy. Methods: In this randomized controlled trial, 114 patients (mean age: 38.9 ± 9.0 years) scheduled for colposcopically directed cervical punch biopsy were randomly assigned to local anesthesia (n = 39), forced coughing (n = 39) and control (n = 36) groups. Pain perception was measured on a 10-cm visual analog scale (VAS) during the insertion of the speculum, injection of the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Most patients can tolerate pain to complete necessary procedures but studies show that pain scores are often high.. Cervical biopsy and cervical curettage are associated with visual analogue scale (VAS) pain scores ranging from four to six on a 10-point scale. (1, 2) Endometrial biopsies done have VAS scores of five to seven(3, 4). Pain with intrauterine device (IUD )insertion varies from two to seven, (58) and pain scores during laminaria insertions with paracervical block range from five to seven.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients can tolerate pain to complete necessary procedures but studies show that pain scores are often high.. Cervical biopsy and cervical curettage are associated with visual analogue scale (VAS) pain scores ranging from four to six on a 10-point scale. (1, 2) Endometrial biopsies done have VAS scores of five to seven(3, 4). Pain with intrauterine device (IUD )insertion varies from two to seven, (58) and pain scores during laminaria insertions with paracervical block range from five to seven.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of pain associated with this procedure, as reported in published studies, varies from mild to severe . The effects of various anesthetic and analgesic approaches for pain relief during colposcopy and cervical biopsy have been examined in many studies . While the use of topical anesthetic gel and oral analgesic drugs appeared ineffective in this situation, it was evident that intracervical submucosal injection of lidocaine could reduce pain severity .…”
Section: Introductionmentioning
confidence: 99%
“…Cervical biopsy and cervical curettage are associated with visual analog scale (VAS) pain scores ranging from four to six on a 10-point scale. 1,2 Endometrial biopsies have been reported to have VAS scores of five to seven. 3,4 Fractional curettage is a common procedure for investigating the causes of abnormal uterine bleeding in perimenopausal women.…”
Section: Introductionmentioning
confidence: 99%